Case Report: Prompt Management in 35 Years Old Man with Vascular Injury at The Level of Brachialis Artery - Amijaya, Dody Tisna; Ismail, Darmawan (Syntax Corporation, 2025)
Penetrating trauma to the upper extremity frequently causes vascular injuries, often involving nerves and tendons, with the brachial and ulnar arteries being critical for arm function, necessitating prompt and effective management. This study reports on the management of brachial and ulnar artery injury due to penetrating trauma. A 35-year-old man sustained lacerations to the right upper and lower arm from broken glass, leading to numbness in the fingers and absent ulnar pulse. Examination revealed hypesthesia, limited range of motion, and absent SpO2 readings in the third to fifth fingers, with angiography showing a proximal brachial artery gap and nearly empty ulnar artery flow. The patient underwent emergency surgery, where exploration revealed severed flexor tendons, muscles, and ulnar artery. Thrombectomy and vascular anastomosis were performed, successfully restoring blood flow. The procedure was completed without complications, and the patient showed satisfactory post-surgical outcomes. Forearm arterial injuries require prompt diagnosis and surgical repair, as timely intervention within 6–12 hours improves long-term outcomes by preserving circulation, preventing ischemic damage, and maintaining limb function.